Evaluating Public Participation in a Deliberative Dialogue: A Single Case Study - Tiffany Scurr; Rebecca Ganann; Shannon L. Sibbald; Ruta Valaitis; Anita Kothari (Kerman University of Medical Sciences, 2022)
Background  Deliberative dialogues (DDs) are used in policy-making and healthcare research to enhance knowledge exchange and research implementation strategies. They allow organized dissemination and integration of relevant research, contextual considerations, and input from diverse stakeholder perspectives. Despite recent interest in involving patient and public perspectives in the design and development of healthcare services, DDs typically involve only professional stakeholders. A DD took place in May 2019 that aimed to improve the social environment (eg, safety, social inclusion) and decrease social isolation in a rent-geared-to-income housing complex in a large urban community. Tenants of the housing complex, public health, primary care, and social service providers participated. This study aimed to determine how including community tenants impacted the planning and execution of a DD, including adjustments made to the traditional DD model to improve accessibility.Methods  A Core Working Group (CWG) and Steering Committee coordinated with researchers to plan the DD, purposefully recruit participants, and determine appropriate accommodations for tenants. A single mixed-methods case study was used to evaluate the DD process. Meeting minutes, field notes, and researchers' observations were collected throughout all stages. Stakeholders' contributions to and perception of the DD were assessed using participant observation, survey responses, and focus groups (FGs).Results  34 participants attended the DD and 28 (82%) completed the survey. All stakeholder groups rated the overall DD experience positively and valued tenants' involvement. The tenants heavily influenced the planning and DD process including decisions about key DD features. Suggestions to improve the experience for tenants were identified.Conclusion  These findings demonstrate the viability of and provide recommendations for DDs involving public participants. Like previous DDs, participants found the use of engaged facilitators, issue briefs, and off-the-record deliberations useful. Similarly, professional stakeholders did not highly value consensus as an output, although it was highly valued among tenants, as was actionability.